2019
DOI: 10.1007/s11938-019-00242-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Behind Folds Visualizing Techniques and Technologies in Improving Adenoma Detection Rate

Abstract: contains supplementary material, which is available to authorized users. Keywords Colorectal cancer I Adenoma detection rate I Adenoma miss rate I Behind folds visualizing technique I Cap-assisted colonoscopy I EndoRings I Endocuff Vision I Extra Wide Angle View (EWAVE) I Full Spectrum Endoscopy (FUSE) I Third Eye Panoramic cap I Third Eye Retroscope I Scope retroflexion I Systematic review I Meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…On the other hand, maneuverability may be expected to be more difficult with EndoRings, which is characterized by a bulkier shape with three circular rows of flexible silicone‐rubber rings 25 . However, both cecal intubation rate (RR 1.00, 0.99–1.01) and cecal intubation time (mean difference 0.20 min, −0.34 to 0.74) were similar between the two groups in our meta‐analysis, probably owing to the high experience of the endoscopists involved in the included trials.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, maneuverability may be expected to be more difficult with EndoRings, which is characterized by a bulkier shape with three circular rows of flexible silicone‐rubber rings 25 . However, both cecal intubation rate (RR 1.00, 0.99–1.01) and cecal intubation time (mean difference 0.20 min, −0.34 to 0.74) were similar between the two groups in our meta‐analysis, probably owing to the high experience of the endoscopists involved in the included trials.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Shirin et al [57] found that the technique yielded a higher detection rate of adenomas/polyps (ADR and PDR), including well-formed, flat and sessile serrated ones, when compared to SC. When meta-analysed with a previously published paper by Halpern et al [58], Keulen et al [59] discovered that ADR by means of the G-Eye endoscope is 30% higher than SC.…”
Section: Non-robotic Colonoscopes and Colonoscopy Adjuncts In The CLImentioning
confidence: 99%
“…27 A recent systematic review and meta-analysis looking at 'behind fold visualising techniques' including cap-assisted ENDOCUFF VISION, EndoRings and FUSE showed no improvement in ADR compared with conventional colonoscopy although there was a significant improvement with G-Eye (Pentax, Japan) with an RR of 1.3. 28 Although colonoscopy remains the gold standard for investigation of the colon, there are those who are unable to tolerate complete optical colonoscopy. Other options for luminal screening include computed tomographic (CT) colonography and colon capsule endoscopy.…”
Section: Improving Lesion Detectionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis looking at ‘behind fold visualising techniques’ including cap-assisted ENDOCUFF VISION, EndoRings and FUSE showed no improvement in ADR compared with conventional colonoscopy although there was a significant improvement with G-Eye (Pentax, Japan) with an RR of 1.3. 28…”
Section: Improving Lesion Detectionmentioning
confidence: 99%